Studi Komparatif Implementasi Manajemen Pembelajaran Daring Pada Satuan Pendidikan Formal dan Nonformal - Lelatobur, Lovely Ezverenzha; Nurwidayati, Pityarini; Satyawati, Sophia Tri (Jurnal Paedagogy, 2023)
This study aims to describe the performance of POAC management functions in the online learning process during the COVID-19 pandemic at Satya Wacana Christian High School Salatiga and PKBM Life Community School West Jakarta. The research method used a descriptive with a qualitative approach. The subjects of this study were teachers in each of the research schools. Data collection was conducted through interviews, observations, and literature studies. The data analysis technique of this research was interactive analysis consisting of data reduction, data display, conclusion and verification. Results showed that each school’s POAC stage of online learning implementation faced challenges. However, all stakeholders’ synergy and active roles were deployed to overcome the challenge in each stage by providing teachers with the necessary equipment, training, and access to the internet for the learning process. Problems found during the process were learners’ focus, material delivery methods that cause boredom, inadequate software, gadgets, and internet connection. Some solutions implemented are modifying the learning approach from teacher-centred to student-centred, modules, presentations, questions and answers, projects, and parents’ involvement are also provided to manage the problems.